Effects of Group Psychoeducation on Knowledge of Caregivers of People with Schizophrenia - Raviteja Innamuri; Karunakaran Palani; Margaret Silas; Reema Samuel; Donae E. George; Visalakshi Peravali; Deepa Ramaswamy (Indian Journal of Psychiatric Nursing)
Background: Several studies have documented poor knowledge of schizophrenia among caregivers and its negative influence on clinical outcomes such as treatment response and prognosis. The benefits of group psychoeducation of caregivers of patients suffering from schizophrenia have been well established. However, very few studies have explored the effectiveness of the group psychoeducation program in the Indian setting. Aims: This study aims to evaluate the effects of a group psychoeducation program on the knowledge of schizophrenia among caregivers. Settings and Design: The study was conducted at the department of psychiatry at a tertiary care hospital. The study design is a quasi-experimental, two-group pretest posttest design. Methods: Sixty-eight caregivers fulfilling the inclusion criteria were recruited consecutively from the inpatient wards. Their knowledge was assessed with a Knowledge About Schizophrenia Interview (KASI) questionnaire, within 1 week of admission and again during the week of discharge. Controls were caregivers who received psychoeducation through “standard care” alone. Cases were caregivers who received the “group psychoeducation program” in addition to the “standard care” during the course of their stay at the hospital. Their pretest and posttest scores were compared. Results: Fifty caregivers successfully completed the study. There was statistical difference between cases and controls in education (P = 0.007) and duration of stay (P ≤ 0.001). Comparing pretest and posttest scores of all the participants showed that psychoeducation received through various sources (standard care or standard care with group psychoeducation) from admission until discharge produced a significant change in knowledge (P = 0.001). On controlling for education and duration of inpatient stay using multivariate analysis, group psychoeducation further produced a significant improvement in KASI scores in subsections of management (B = 0.839, confidence interval [CI] = 0.301–1.377, P = 0.002) and course and prognosis (B = 1.366, CI = 0.095–2.637, P = 0.035). Conclusions: Group psychoeducation in the Indian setting is an effective and feasible option to improve the knowledge of schizophrenia among caregivers, especially with regard to management, course, and prognosis.